Fiebre por mordedura de rata: Reporte de un caso probable en el Hospital Regional del Cuzco. - CABADA SAMAME, Miguel (2013)
4 year old patient was admitted to the Emergency Department of Hospital Regional de Cusco with 17 days history of a rat bite. One week later, the patient developed fever and rash, which lasted for 3 days. Fever, an abscess on the forehead with lymphangitis, and cervical lymphadenopathy were observed on admission. The VDRL test was positive but FTA-Abs was negative. He was diagnosed of rat bite fever and treated with IV penicillin G with a favorable response. The case is discussed and pertinent literature is reviewed.